Sex testing in women's sport: historical harms, contemporary risks, and World Athletics' 2025 policy shift - Camporesi, S.; Mazzucco, M.; Patiño, M. J. M.; Ospina-Betancurt, J.; Teetzel, S. (Frontiers in Sports and Active Living, 2026)
The history of systemic, mandatory sex testing of all women athletes in sport is now well documented, with hundreds of articles, entire books, and doctoral dissertations analyzing the scientific, legal, and ethical aspects of sports governing bodies' determination to verify that competitors in the women's event were women and that men did not sneak into women's sports. A 30 July 2025 press release from World Athletics (WA), announcing changes to its eligibility rules for competing in female events is momentous for three reasons. First, in referring to women's events specifically and exclusively as female events it signals that the organization prioritizes biological sex, not gender, in its eligibility considerations. Second, it merges regulations for women with variations of sex characteristics 1 and transgender women into one set of regulations, ignoring the differences between these two groups of women athletes. Finally, it marks the return of systemic sex testing for all elite women athletes competing in track and field, a practice that ended in the 1990s for good reasons, given the substantial legal, ethical, and cultural objections voiced by a myriad of medical and scientific bodies, as well as by athletes who bravely shared their experiences. In critically examining WA's press release outlining its decision to reinstate systemic sex testing through mandatory screening of the Sex-determining Region Y (SRY) gene for all high-performance women track and field competitors, we demonstrate how these regulations reproduce patterns of harm condemned by experts in the fields of medicine, ethics, and human rights. We conclude that WA's July 2025 decision fails to address the cogent arguments that led to the cessation of systemic sex testing in 1999, contravenes human rights laws, and anachronistically reintroduces harmful practices that were abandoned for good reasons.